The dynamic specification of the inflation model in Zimbabwe - Sunde, Tafirenyika (Midlands State University, 2015)
In order to estimate the inflation function in Zimbabwe we used cointegration and error-correction mechanism (a methodology popularized by Hendry etal (1989)). This approach has received extensive empirical support. Right now the approach seems to have generally settled the long-standing problem over the instability of the inflation model (function). Using the above technique, we managed to come up with a stable inflation model for Zimbabwe. This study also established that one must go beyond a simple monetary account of the inflation process even if inflation will always have a monetary dimension. Other factors that were found to be significant in explaining inflation in Zimbabwe are: real output, budget deficit, exchange rate depreciation and interest rates. The results that we got fitted very well all the theoretical priors, and they also concur with the studies done elsewhere for both the developed and the developing countries. Introduction